The 1st International Conference on Net-Zero Built Environment Innovations in Materials, Structures, and Management Practices - Kioumarsi, Mahdi; Shafei, Behrouz; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book provides the latest fundamental and practical advances in reducing the built environment$1 (Bs carbon footprint based on a collection of papers presented at the 1st International Conference on Net-Zero Built Environment: Innovations in Materials, Structures, and Management Practices, held June 19-21, 2024, in Oslo, Norway. The volume presents research investigations and case studies spanning five interrelated domains: New materials and material preparation processes for zero (or negative) carbon footprint Robotic construction technologies for minimum formwork and on-site activities Novel structural designs and details for optimal performance with the least material usage Advanced condition assessment and health monitoring methods for the longest service life Innovative life-cycle analysis and policy-making strategies for effective civil infrastructure management.s
Life Cycle Management and Probabilistic Levelized Cost of Energy Analysis of Floating Offshore Wind Farms -- An Experimental Study of Consistency and Strength Variation of 3D Printed Concrete Mixes -- Post Project Evaluation a Perspective for Effective and Sustainable Healthcare Design -- Smart Technologies New Perspectives for the Heritage Environment -- Effects of Low carbon Binders on the Mechanical and Thermal Properties of Bio-based Insulation Materials -- Decarbonizing Building Materials for Net Zero Emissions A Feasibility Study in Canada.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sustainable architecture; Building materials; Control engineering; Robotics; Automation; Environmental engineering; Civil engineering; Sustainable Architecture/Green Buildings; Building Materials; Control, Robotics, Automation; Environmental Civil Engineering; Civil Engineering; Structural Materials